HUBUNGAN ANTARA MAQĀṢID AL-SYARĪ’AH DENGAN BEBERAPA METODE PENETAPAN HUKUM (QIYĀS DAN SADD/FATH AL-ŻARĪ’AH) - Halim, Fatimah (State Institute of Islamic Studies (IAIN) Palu, 2010)
This articleÂ discussesÂ theÂ relationshipÂ betweenÂ maqÄá¹£id al-syarÄ«'ahÂ withÂ severalÂ methods ofÂ determiningÂ the law.Â The object of theÂ studyÂ is limitedÂ to twoÂ modelsÂ of law, namely qiyÄs andÂ sadd (fath) Â al-Å¼arÄ«'ah.Â This problemÂ was discussed throughÂ library research byÂ usingÂ theÂ comparative method. The resultsÂ showedÂ that, the method ofÂ determination ofÂ the law,Â eitherÂ through qiyÄs Â andÂ sadd (fatá¸¥)Â al-Å¼ari'ahÂ haveÂ a very close relationship withÂ maqÄá¹£id al-syarÄ«ah.Â In theÂ qiyÄsÂ method,Â maqÄá¹£idÂ al-syarÄ«'ah is an important factor in assessingÂ the illat, whereas in theÂ method ofÂ al-Å¼ari'ah, maqÄá¹£idÂ al-syarÄ«'ahÂ it is Â saddÂ al-Å¼arÄ«ahÂ orÂ fathÂ al-Å¼arÄ«'ah as a determinant factor.Kata Kunci: maqÄá¹£id al-syarÄ«ah, qiyÄs, sadd al-Å¼arÄ«â€™ah, fatá¸¥ al-Å¼ariâ€™ah